THE EFFECT OF ADDING ANHYDROUS ACETIC ACID TO PREPARE WHEY PROTEIN CONCENTRATES TO IMPROVE ITS FUNCTIONAL PROPERTIES. - Mohammed, Atheer Jasim (Diyala Agricultural Sciences Journal, 2013)
Two types of whey protein concentrates were prepared, One was from sour whey and the other from salted or unsalted sweet whey. They were acetylated by different concentrations and their effectiveness properties were studied. It was found that the sour whey(unsalted and acetylated) exceeded its counterpart of treatments in the percentage of moisture and ash. However, the salted and unsalted sweet whey(acetylated) had significant superiority over other treatments, in the following properties; total protein, foam size, gel formation, oil and water absorption, and the emulsification properties. Thus, the results showed that the 0.5٪ of acetylation for salted and unsalted sweet and sour whey proteins was the best in changing the functional properties of the acetylated whey protein concentrates compared to the acetylation percentage 0.3٪ and 0.9٪, respectively. In addition, the salt effect in most treatments has shown a significant effect. So, the above results showed that salted sour and sweet whey protein are the best in the process of acetylation because of its improvement of functional and chemical properties.